2010
DOI: 10.1016/j.jlumin.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved cathodoluminescence study of zinc oxide nanorods catalytically grown on p-type 4H-SiC

Abstract: Optical properties of ZnO nanorods (NRs) grown by vapour-liquid-solid (VLS) technique on 4H-p-SiC substrates were probed by cathodoluminescence (CL) measurements at room temperature and at 5 K complemented with electroluminescence. At room temperature the CL spectra for defect related emission intensity was enhanced with the electron beam penetration depth. We observed a variation in defect related green emission along the nanorod axis. This indicates a relatively poor structural quality near the interface bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…As the accelerating voltage is increasing the depth of penetration of the beam is increasing. The DLE peak intensity of the ZnO nanorods was observed to increase linearly as the accelerating voltage is increased and at relatively high accelerating voltages it starts to saturate [45]. The same is also observed regarding the NBE peak intensity (see Figure 9(b)).…”
Section: Cathodoluminescence Spectroscopysupporting
confidence: 73%
“…As the accelerating voltage is increasing the depth of penetration of the beam is increasing. The DLE peak intensity of the ZnO nanorods was observed to increase linearly as the accelerating voltage is increased and at relatively high accelerating voltages it starts to saturate [45]. The same is also observed regarding the NBE peak intensity (see Figure 9(b)).…”
Section: Cathodoluminescence Spectroscopysupporting
confidence: 73%
“…This reabsorbed UV can excite the defect states in the structures, resulting in visible deep band emission because the defects responsible for this emission are not confined near the surface but are ubiquitous inside the ZnO NRs [29]. Previously, we have reported that the UV emission from ZnO NRs can be internally reabsorbed within 2 μm [35,36]. Figure 10 shows that the EL spectra of ZnO NRs grown on a rGO-modulated seed exhibited two emission peaks: a violet peek at 430 nm and a green emission centered at 530 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above the trap concentration observed in ZnO NRs (2.9 × 10 17 cm –3 ) is two orders of magnitude higher than that observed for ZnO NTs (3.3 × 10 15 cm –3 ). According to two separate recent investigations using high‐resolution electron microscopy (HR‐TEM) 25 and depth‐resolved cathodoluminescnce (CL) 26, it was shown that the density of defects is higher near the substrate than further up in ZnO NRs, i.e., along the growth direction. Moreover, as the growth of the ZnO NRs was achieved using a seed layer, which upon heating to 250 °C dissociate to form ZnO nanoparticles of a size 90 nm 27 initiating the growth, a radial dependence of the traps is also expected.…”
Section: Resultsmentioning
confidence: 99%